Neurotrophin, p75, and Trk Signaling Module in the Developing Nervous System of the Marine Annelid Platynereis dumerilii. (16th March 2016) - Lauri, Antonella; Bertucci, Paola; Arendt, Detlev
Abstract : In vertebrates, neurotrophic signaling plays an important role in neuronal development, neural circuit formation, and neuronal plasticity, but its evolutionary origin remains obscure. We found and validated nucleotide sequences encoding putative neurotrophic ligands (neurotrophin, NT) and receptors (Trk and p75) in two annelids, Platynereis dumerilii (Errantia) and Capitella teleta (Sedentaria, for which some sequences were found recently by Wilson, 2009). Predicted protein sequences and structures of Platynereis neurotrophic molecules reveal a high degree of conservation with the vertebrate counterparts; some amino acids signatures present in the annelid Trk sequences are absent in the basal chordate amphioxus, reflecting secondary loss in the cephalochordate lineage. In addition, expression analysis of NT, Trk, and p75 during Platynereis development by whole-mount mRNA in situ hybridization supports a role of these molecules in nervous system and circuit development. These annelid data corroborate the hypothesis that the neurotrophic signaling and its involvement in shaping neural networks predate the protostome-deuterostome split and were present in bilaterian ancestors.